2020
DOI: 10.3233/jad-191257
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cerebral Microbleeds with Cognitive Decline: A Longitudinal Study

Abstract: Background: The role of cerebral microbleeds (CMBs) in cognitive impairment remains controversial. Objective: To investigate the possible links between the presence, progression, number, and location of CMBs and cognition. Methods: We assessed 792 subjects from the Alzheimer's Disease Neuroimaging Initiative who underwent both brain 3 Tesla MRI scans and cognitive testing. The association between CMBs and cognitive change was explored using linear mixed-effects models (LME).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 31 publications
0
15
0
1
Order By: Relevance
“…The effect of cerebrovascular disease on cognition may be modulated by carriage of the APOE ε4 allele, which has far‐reaching effects via numerous Aβ‐dependent and independent pathways. Some studies reported APOE ε4‐independent associations between vascular disease and AD biomarkers 90,96 and/or cognitive decline 90,101 . However, in a study conducted in the Sunnybrook Dementia Cohort and replicated in ADNI, 102 greater WMH volume was associated with worse attention/executive functions and language in APOE ε4 carriers but not non‐carriers across the spectrum of AD and dementia with Lewy bodies.…”
Section: Beyond At(n): Other Influences On Disease Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of cerebrovascular disease on cognition may be modulated by carriage of the APOE ε4 allele, which has far‐reaching effects via numerous Aβ‐dependent and independent pathways. Some studies reported APOE ε4‐independent associations between vascular disease and AD biomarkers 90,96 and/or cognitive decline 90,101 . However, in a study conducted in the Sunnybrook Dementia Cohort and replicated in ADNI, 102 greater WMH volume was associated with worse attention/executive functions and language in APOE ε4 carriers but not non‐carriers across the spectrum of AD and dementia with Lewy bodies.…”
Section: Beyond At(n): Other Influences On Disease Progressionmentioning
confidence: 99%
“…Some studies reported APOE ε 4-independent associations between vascular disease and AD biomarkers 90 , 96 and/or cognitive decline. 90 , 101 However, in a study conducted in the Sunnybrook Dementia Cohort and replicated in ADNI, 102 greater WMH volume was associated with worse attention/executive functions and language in APOE ε 4 carriers but not non-carriers across the spectrum of AD and dementia with Lewy bodies. Neuropathological assessment revealed that 100% of APOE ε 4 homozygotes but only 64% of heterozygotes had cerebral amyloid angiopathy, suggesting that accumulation of A β in the cerebral vasculature may be the etiology for WMH in APOE ε 4 carriers.…”
Section: Beyond At(n): Other Influences On Disease Progressionmentioning
confidence: 99%
“…The prevalence of CMBs is significantly higher in the elderly population with multiple comorbidities and high-total cardiovascular risk, especially hypertension with subsequent hypertensive arteriopathy (13,14). Usually, CMBs are clinically silent in the terms of acute stroke care but might have a cumulative impact on patients in the following years, mainly because of the associations between the load of CMBs and cognitive impairment (15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…CC-BY 4.0 International license It is made available under a is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity. (which was not certified by peer review) 14), but associations between PVS and poorer cognitive ability, either cross-sectionally or longitudinally, are more variable (12). In recent years, several studies have quantified the 'total brain burden' of SVD using a simple 0-4 score, which allocates one point for the presence of each SVD marker (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the presence of lacunes and microbleeds have been associated with cognitive decline (12)(13)(14), but associations between PVS and poorer cognitive ability, either cross-sectionally or longitudinally, are more variable (12). In recent years, several studies have quantified the 'total brain burden' of SVD using a simple 0-4 score, which allocates one point for the presence of each SVD marker (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%